The Heroic Journey in Popular Culture - Karki, Dhruba (Tribhuvan University Journal, 2016)
Popular culture integrates people in diverse settings. Individuals share ideas through materials they use, including food, dresses, movies, magazines, and holiday spots. In the past, people set for pilgrimage to holy sites; these days, they go on trekking through hills. Pilgrimages to consecrated sites have been replaced by people’s journey to discotheque, fashion center and shopping complex in the modern time corporate world. What binds them together is the transformation of consciousness in line with the journey from the terrestrial to the celestial sphere. Specific human activities, including pilgrimage and business trip become popular culture when people make them significant parts of their lives. Sound and images of disco, jazz, hip-hop, and pop-rock have entered the streets and hotels equally in cities of the industrial world, from Lhasa to London, Karachi to Kathmandu, and Tokyo to New York, irrespective of their cultures and ethnic backgrounds. In today’s world of saturated media presence, images and icons of heroes and legends, motivated by commercial and popular appeal, are circulated with a greater speed, becoming simultaneously a shared mythic currency and continuity, the modern world embodiment of silk road business, and thus, crossing the East-West divide.